1998
DOI: 10.1002/(sici)1098-2744(199803)21:3<156::aid-mc2>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of neu differentiation factor–like polypeptides bycph-transformed fibroblasts: Cloning and characterization of Syrian hamster neuregulin cDNAs

Abstract: We reported previously that expression of the cph oncogene in Syrian hamster and mouse cells leads to the secretion of a polypeptide factor or factors structurally and functionally related to neu differentiation factor (NDF) and the establishment of an autocrine loop mediated through the simultaneous overexpression of the erbB4 receptor. To identify the nature of this factor and to characterize its role in the neoplastic conversion of Syrian hamster embryo cells, we cloned cDNAs hybridizing to rat NDF-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
1999
1999

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…These studies showed that expression of the cph oncogene in Syrian hamster and mouse cells leads to the establishment of an autocrine loop mediated by the simultaneous secretion of an a2b-neuregulin and the increased expression of the erbB2 or erbB4 receptors (Avila et al, 1995;Velasco et al, 1998). These results support the notion that autocrine neuregulin signaling plays an important role in maintaining the transformed phenotype by providing a growth advantage to the cph-transformed cells.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…These studies showed that expression of the cph oncogene in Syrian hamster and mouse cells leads to the establishment of an autocrine loop mediated by the simultaneous secretion of an a2b-neuregulin and the increased expression of the erbB2 or erbB4 receptors (Avila et al, 1995;Velasco et al, 1998). These results support the notion that autocrine neuregulin signaling plays an important role in maintaining the transformed phenotype by providing a growth advantage to the cph-transformed cells.…”
Section: Introductionmentioning
confidence: 73%
“…In this regard, it is important to note that we have shown previously that one of the most immediate phenotypic consequences of the endogenous (in Syrian hamster embryo cells) or heterologous (in NIH3T3 cells) expression of the cph oncogene is the establishment of a hyperactive autocrine loop mediated by the secretion of a neuregulin and the overexpression of the erbB4 or erbB2 neuregulin receptors (Avila et al, 1995;Velasco et al, 1998). In the course of experiments designed to characterize this autocrine loop cells were maintained under conditions of serum deprivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the inhibitory effect on primary culture was less prominent than that on L6 cell line. It may be explained by the observation that the primary cultures of rat myoblasts were significantly contaminated by fibroblasts (less than 30% of total cell number at the time of plating and more than 60% 2 days after plating), which are known to secrete NRGs (31,32). Another explanation could be the heterogeneity in the population of rat primary myoblasts, a part of which might have already committed to differentiation program at the time of the preparation of the primary cultures.…”
Section: Inhibition Of Nrg Receptor Activation Suppresses the Differementioning
confidence: 99%
“…These factors continue to act as needed during adult life for tissue renewal and wound repair. Oncogenic ras transformation of mouse ®broblasts (Alimandi et al 1995), or cph transformation of Syrian hamster embryo cells (Avila et al 1995), results in a hyperactive autocrine loop mediated by overexpression of neuregulin proteins that contribute to the transformed phenotype (Velasco et al 1998). Transformation of murine or human breast cell lines with mutation-activated or over-expressed wildtype p185 neu also results in autocrine, juxtacrine and paracrine expression of multiple neuregulin proteins (Minicione et al 1996;Ethier et al 1996;Sepp-Lorenzino et al 1996).…”
Section: Discussionmentioning
confidence: 99%